Sanksi Terhadap Pelanggar Izin Usaha Pada Industri Rumah Makan - Pande Putu Dinda Novita Wijaya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2025)
A restaurant is a business that provides food and drinks for customers. Business opportunities for restaurants have broad market potential because food and drink are the basic needs of every individual. In this study the authors will discuss 1) the legal arrangements for business licences in the restaurant industry? and 2) how the sanctions against violators of business licences in the restaurant industry?. The research method used in this research is normative legal method. Based on the research obtained, in establishing a restaurant, a licence is required in accordance with applicable regulations, the licence will be grouped according to the level of business risk. Although there are regulations governing this sector, cases of licence violations are still very common in the community. As a result, business actors who violate the rules will be subject to administrative sanctions in the form of warnings, temporary suspension of operations through freezing business licences, fines, use of force by police officers, and revocation of company licences. In this case, the government should apply strict legal sanctions against violations of restaurant business licences, and business actors should have awareness in taking care of their business licence ownership.